Very Preterm Birth, Cerebellar Development and Neuropsychological Outcome in Adolescence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Cerebellar volumes were measured on structural MRI at adolescence and adulthood in 65 preterm individuals (born before 33 weeks' gestation), and a term-born comparison group, in a study at King's College, Great Ormond Street Hospital, and University College, London; and Seoul National University College of Medicine, Korea.